2017
DOI: 10.1371/journal.pone.0176569
|View full text |Cite|
|
Sign up to set email alerts
|

Preventive child health care at elementary school age: The costs of routine assessments with a triage approach

Abstract: BackgroundTriage in Preventive Child Health Care (PCH) assessments could further the efficient use of human resources and budgets and therefore make extra care possible for children with specific needs. We assessed the costs of routine PCH assessments with and without triage for children aged 5/6 years and 10/11 years. In a triage approach, PCH assistants conduct pre-assessments to identify children requiring follow-up assessments by a physician or nurse. In the usual approach, all children are assessed by a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…20 Our study of the costs of the routine assessments in the two approaches showed that the triage approach resulted in a cost reduction of about one-third for the age group of 5 to 6 years and a minimal cost reduction for the age group of 10 to 11 years. 21 This study examined the impact of triage and task shifting on care for children at risk who were identified by PCH or by external parties such as parents and schools. It addresses the following research questions:…”
mentioning
confidence: 99%
“…20 Our study of the costs of the routine assessments in the two approaches showed that the triage approach resulted in a cost reduction of about one-third for the age group of 5 to 6 years and a minimal cost reduction for the age group of 10 to 11 years. 21 This study examined the impact of triage and task shifting on care for children at risk who were identified by PCH or by external parties such as parents and schools. It addresses the following research questions:…”
mentioning
confidence: 99%